2013
DOI: 10.1179/1743281212y.0000000067
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of iron losses during desulphurisation of hot metal utilising nepheline syenite

Abstract: Iron losses during calcium carbide based hot metal desulphurisation have been studied via large scale investigations of slag from the slag pit as well as slag sampling during desulphurisation at SSAB EMEA in Luleå . The desulphurisation slag, after injection of calcium carbide, is normally solid and contains large amounts of iron. An alkali containing mineral, nepheline syenite, was mixed together with the calcium carbide to form a more fluid slag as the iron losses originate from enclosed metal droplets in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(38 citation statements)
references
References 9 publications
2
36
0
Order By: Relevance
“…This is due to significant increase splashes of hot metal during desulfurization. This result is in good agreement with the data obtained in the ref . Therefore, a minimization of iron losses with metal droplets in the slag in the trials with a NS injection should be done by an optimization of the gas injection.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This is due to significant increase splashes of hot metal during desulfurization. This result is in good agreement with the data obtained in the ref . Therefore, a minimization of iron losses with metal droplets in the slag in the trials with a NS injection should be done by an optimization of the gas injection.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, several plant trials showed that the injection of NS during desulphurization of the hot metal can significantly reduce the iron losses in slag. For instance, the magnetic fraction in the skimmed slag after desulfurization of hot metal, which correlates to the iron losses in this slag, decreases in the heats with an injection of NS by 54.5% on average for fractions of slag pieces in the size range from 5 to >300 mm . This decrease of the magnetic iron losses in the slag from 2.5 to 1.9% was explained by a more effective slag skimming in the trials with an addition of NS.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Overall, the amount of iron losses in a slag only during desulfurization operations (Source 1) can reach from 30-60% 5) to 80% 4) (6-11 kg/t HM) from the summary iron losses during desulfurization of hot metal depending on the used technology. Therefore, the purposes of this study were: a) to characterize the metal droplets in the size range smaller than 5 mm in the slag just after desulfurization of hot metal, b) to consider the different mechanisms of involving of different metal droplets into the slag during the desulfurization process, c) to discuss the effects of some technological parameters of desulfurization on a possibility to decrease the amounts of different metal droplets in the slag.…”
Section: Introductionmentioning
confidence: 99%
“…Magnelöv et al 5) estimated the total iron losses and quotas of magnetic fractions having different sizes in the skimmed slag after desulfurization of hot metal by injection of CaC2 + 2 wt% cryolite (Campaign 1) and CaC2 + 5 wt% nepheline syenite (Campaign 2). The magnetic fractions in the skimmed slags after desulfurizations (Sources 1 and 2) in Campaign 1 (average reduction of S content in the iron was from 0.026% to 0.0051%) and Campaign 2 (average reduction of S content in the iron was from 0.044% to 0.0037%) were 2.5 and 1.9% of the total processed hot metal, respectively.…”
Section: Introductionmentioning
confidence: 99%